Representing Configuration Model Based on Organizational Culture (Market and Club) for Active Companies in Tehran Stock Exchange - Mohammad Mozhdeh, Mohammad Hosein Vadeei Noghabi, Mojtaba Moshdeei (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It seems that organizational culture is an inseparable part of a company. Organizational culture may be configured based on its investigated dimensions. Organizational culture configuration helps the activities of companies increase and finally they enjoy higher advantages. Therefore, this study aims at investigating the configuration model based on organizational culture (market, club) for active companies in Tehran Stock Exchange. PLS Structural Equation Modeling (SEM) used as methodology in this study. The statistical population are the employers of exchange. Random systematic sampling method was used. The sample volume is 220 of Tehran Stock Exchange experts. The current study is applied in purpose and analytical-descriptive in methodology and with correlation approach and estimation in Partial Least Squares regression (PLS). The research findings show that the factor analysis values of all items are more 0.4 and so measurement model is a homogenous model and factor analysis values are acceptable. P-value results showed t-statistic is more than 2.58 for all items. It means that the relationship among items is accepted with the related latent variable at 99% confidence level.